Prevalence of ectoparasites in free-range backyard chicken flocks in northeast Algeria - Nahal, Amir (Array, 2021)
Free-range backyard chicken breeding is gaining popularity in Algerian rural regions. Due to the natural rearing conditions, chickens are exposed a wide range of microbes and ectoparasites. Currently, little is known about the variety of ectoparasites infesting free-range chickens in Algeria. The present study was conducted over a two year period on 169 backyard chicken, with the aim of identifying and estimating the prevalence of ectoparasites on different body parts of the chickens, and their immediate environments in northeast Algeria. In total, 9943 ectoparasites were identified, and the seven most dominant species were: Menopon gallinae (82.84%), Goniodes dissimilis (15.97%), Menacanthus stramineus (13.60%), Goniocotes gallinae (6.50%), Lipeurus caponis (5.23%), Argas persicus (9.46%) and Dermanyssus gallinae (1.18%). Menopon gallinae was the most frequent isolated ectoparasite throughout the year. Soft ticks Argas persicus were isolated during spring and summer, mainly from crevices and cracks, while the chicken red mite Dermanyssus gallinae was detected in autumn with a low load on bird body parts and a high abundance in nests. These results list the most abundant ectoparasites in backyard chickens, which could facilitate the improvement of rearing management.